Formulating design guidelines for cultural heritage multimedia systems with byzantine art content - Voutounos, Chrysanthos; Zaphiris, Panayiotis; Lanitis, Andreas (My University, 2011)
The development of future multimedia systems for the presentation and preservation of Byzantine art necessitates the formulation of special design guidelines, which brings Byzantine art and new technologies in a constructive technocultural symbiosis. The e-learning and pedagogical effectiveness of multimedia projects with Byzantine art content, the visualisation of Byzantine imagery, the deeper and devoted research in issues like the aesthetics of Byzantine art, the spiritual communication of Byzantine art promote the need of a technocultural approach synthesized by two distinct elements, multimedia and Byzantine art. With a proposed evaluation experiment for a website with a Byzantine theme, we investigate the reactions and perceptions of young people for Byzantine art, in order to create design guidelines applied on future projects with relevant content. The results of this survey evaluation study, targeting a group of Cypriot young people 15-30 age, superimpose the argument that multimedia e-learning projects specialising in Byzantine art, should promote design strategies that will enchase the communication of Byzantine art in new media.
Keywords: Byzantine art; Multimedia design guidelines; System evaluation; User centred design